Slow TCAM Exhaustion DDoS Attack - Pascoal, Túlio A.; Dantas, Yuri G.; Fonseca, Iguatemi E.; Nigam, Vivek (ICT Systems Security and Privacy Protection, 2017)
Software Defined Networks (SDN) facilitate network management by decoupling the data plane which forwards packets using efficient switches from the control plane by leaving the decisions on how packets should be forwarded to a (centralized) controller. However, due to limitations on the number of forwarding rules a switch can store in its TCAM memory, SDN networks have been subject to saturation and TCAM exhaustion attacks where the attacker is able to deny service by forcing a target switch to install a great number of rules. An underlying assumption is that these attacks are carried out by sending a high rate of unique packets. This paper shows that this assumption is not necessarily true and that SDNs are vulnerable to Slow TCAM exhaustion attacks (Slow-TCAM). We analyse this attack arguing that existing defenses for saturation and TCAM exhaustion attacks are not able to mitigate Slow-TCAM due to its relatively low traffic rate. We then propose a novel defense called SIFT based on selective strategies demonstrating its effectiveness against the Slow-TCAM attack.